KAJIAN DAN TELAAH KRITIS TAFSIR DAN HADITS TENTANG PERCERAIAN - ahsin, moh (Al-Inṣāf, 2024)
Divorce is defined as the dissolution of the marital bond between husband and wife by using the word "talak" or its equivalent. In Indonesia, divorce is regulated in Law Number 1 of 1974 concerning Marriage and KHI. In the Qur'an divorce is explained in detail in Surah al-Thalaq. The method used in this research is normative juridical Surat al-Thalaq in general can be classified into several discussions: First, in verse 1 Allah SWT commands husbands who want to divorce their wives to divorce them during a period of chastity and have not been divorced. Allah SWT also calls for calculating the iddah period that his wife must undergo. Then the prohibition for husbands not to expel their wives during the iddah period from their homes or allow them to leave unless there is a clear violation of the law. Secondly, in verse 2, if the wife is nearing the end of the 'iddah period, then reconcile or divorce her in a good way. Then there is an order that in divorce and reconciliation, two witnesses should be present so that there is no dispute in the future.